A randomized, multicenter, double-blind study to evaluate the safety and efficacy of estradiol vaginal cream 0.003% in postmenopausal women with dyspareunia as the most bothersome symptom. Issue 2 (February 2018) - Kroll, Robin; Archer, David F.; Lin, Yuhua; Sniukiene, Vilma; Liu, James H.
Abstract: Objective: Vulvovaginal atrophy (VVA) is characterized by vaginal changes, dyspareunia, and itching/irritation. Efficacy and safety of a lower-dose estradiol vaginal cream (0.003%) were evaluated in postmenopausal women with VVA-related dyspareunia. Methods: This was a phase 3, randomized, double-blind, placebo-controlled study. Sexually active postmenopausal women with moderate–severe dyspareunia as the most bothersome symptom, ⩽5% vaginal superficial cells, and vaginal pH >5.0 were randomized (1:1) to 0.003% estradiol vaginal cream (15 μg estradiol; 0.5 g cream) or placebo (0.5 g cream) applied daily for 2 weeks followed by three applications/week for 10 weeks. Coprimary outcomes were changes in dyspareunia severity, vaginal cytology, and vaginal pH from baseline to final assessment. Additional efficacy outcomes and safety were assessed. Results: A total of 550 participants (average age, 58 y) were randomized. Compared with placebo, estradiol reduced dyspareunia severity (mean change from baseline ± SD: −1.5 ± 1.0 estradiol vs −1.2 ± 0.9 placebo), decreased vaginal pH (−1.36 ± 0.89 vs −0.53 ± 0.92), and improved vaginal cytology (percentage superficial and parabasal cells 10.1 ± 16.7 vs 1.4 ± 6.1 and −48.5 ± 45.1 vs −14.6 ± 39.6; P < 0.001, all) at the final assessment. In addition, estradiol decreased dyspareunia severity at weeks 8 and 12, vaginal/vulvar irritation/itching at weeks 4 and 12, and dryness at week 12 versus placebo ( P < 0.01, all). VVA severity, pH, and cytology improved at week 12 with estradiol versus placebo ( P < 0.001, all). Vulvovaginal mycotic infections were more frequent with estradiol. One serious event leading to discontinuation occurred with estradiol. No deaths occurred. Conclusions: Lower-dose estradiol vaginal cream (0.003%) dosed three applications/week is an effective and well-tolerated treatment for VVA-related dyspareunia.